Combination of vascular endothelial growth factor-loaded microspheres and hyperbaric oxygen on random skin flap survival in rats - XIE, XUE-GUAN (Exp Ther Med, 2015)
The present study aimed to investigate the role of hyperbaric oxygen (HBO) and treatment with vascular endothelial growth factor (VEGF)-loaded microspheres, and HBO plus VEGF on the survival of random skin flaps in rats. The modified McFarlane flap model was established in 40 rats and evaluated within four groups: VEGF (n=10), HBO (n=10), HBO plus VEGF (n=10) and controls (n=10). Seven days following treatment, the necrotic area of the flap was measured. The specimens were stained with hematoxylin and eosin for histological analysis. Immunohistochemical staining was used to analyze the positive expression levels of VEGF. The percentages of necrosis of the skin flaps in all groups were: 49.66±2.64% in controls, 26.85±1.77% in VEGF, 28.27±2.21% in HBO and 10.44±2.48% in the combination group. Histological analysis demonstrated angiogenesis with mean vessel density per mm(2) in the groups were: 16.68±2.69 in controls, 22.96±3.29 in VEGF, 24.74±3.19 in HBO and 34.81±3.93 in the combination group. The expression of VEGF of the controls, VEGF, HBO and the combination group were 28.33±4.98, 52.54±4.55, 49.32±4.62 and 78.97±4.90 integral absorbance, respectively. For all measurements, the combination group showed greater improvement in random skin flap survival than others (P<0.05). No significant difference was detected between the VEGF and HBO group. The control group exhibited lower survival rates compared with the other groups (P<0.05). Combination of VEGF and HBO improved random skin flap survival compared with the effect of VEGF or HBO alone, suggesting these two agents exhibited a synergistic effect.